Calibration of Gypsum Blocks for Measuring Saline Soils Moisture. Issue 22 (15th December 2016) - Hoseini, Yaser; Albaji, Mohammad
ABSTRACT: The proper management of irrigation requires an accurate measuring of soil moisture. One of the commonly applied methods for measuring soil moisture is the use of gypsum blocks – a method that is simple and quick to apply. However, measuring moisture in saline soils using this method is prone to errors due to the effect of soil salinity on the block. In this study, the effect of different salinities (1, 2, 6, 10, and 18 deci Siemens per meter (dS m −1 ) on the measurements of a gypsum block type 5910 A was investigated with two repetitions in random blocks in sandy loam, loam, and clay loam soils, and corrective functions were obtained using multivariate regression for all soils with different salinity levels. The results showed different trends for measuring the soil moistures for salinities 1–6 dS m −1 compared with salinities 10–18 dS m −1, and the corrective functions in salinities 1–6 dS m −1, which had higher accuracies than those with salinities 10–18 dS m −1 .